2009
DOI: 10.1021/ja909169x
|View full text |Cite
|
Sign up to set email alerts
|

High and Selective CO2 Uptake in a Cobalt Adeninate Metal−Organic Framework Exhibiting Pyrimidine- and Amino-Decorated Pores

Abstract: The synthesis and structure of Co(2)(ad)(2)(CO(2)CH(3))(2) x 2 DMF x 0.5 H(2)O (bio-MOF-11) is described. Pyrimidine and amino groups of adeninate (ad) decorate the pores of the framework. The porosity of this material was studied, and its CO(2) and H(2) adsorption properties were evaluated. bio-MOF-11 exhibits a high heat of adsorption for CO(2) (approximately 45 kJ/mol), a high CO(2) capacity (approximately 6 mmol/g, 273 K), and exceptional selectivity for CO(2) over N(2) at 273 K (81:1) and 298 K (75:1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
490
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 899 publications
(519 citation statements)
references
References 23 publications
23
490
3
3
Order By: Relevance
“…S13 and S14). The value is much higher compared with the next-higher value reported so far (81:1 at 273 K) 4 . Bae et al 38 reported a CO 2 /N 2 selectivity of 95 at 298 K for a carborane-based metal-organic framework.…”
Section: Heats Of Adsorptioncontrasting
confidence: 58%
See 3 more Smart Citations
“…S13 and S14). The value is much higher compared with the next-higher value reported so far (81:1 at 273 K) 4 . Bae et al 38 reported a CO 2 /N 2 selectivity of 95 at 298 K for a carborane-based metal-organic framework.…”
Section: Heats Of Adsorptioncontrasting
confidence: 58%
“…To further understand the pore surface characteristics of the materials and the adsorption process, we have calculated the isosteric heats of adsorption (∆H) for CO 2 and CH 4 . ∆H was calculated using the Clausius-Clapeyron equation from the sorption data collected at 273, 298, and 323 K (refs 4,37).…”
Section: Heats Of Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3c,6-10] Nitrogen-containing groups or open metal sites accessible within the pores can improve CO 2 affinity via dipolequadrupole interactions with the CO 2 molecules. [11][12][13][14] We recently described the material NOTT-122 incorporating triazole groups which displays a high adsorption capacity for CO 2 and used a computational approach to investigate the specific interactions between CO 2 and the framework linker heteroatoms. [15] Similarly, Zaworotko et al have reported MOFs [16] containing amide functional groups in the linkers, whereby linking of three isophthalates generated polyhedral structures that exhibit a strong binding affinity to CO 2 .…”
Section: Introductionmentioning
confidence: 99%